2018
DOI: 10.3928/00220124-20180417-09
|View full text |Cite
|
Sign up to set email alerts
|

Preceptors' Perception of Role Competency

Abstract: Understanding role expectations would benefit both preceptors and nurse educators who select, train, and support nurse preceptors. Identification of essential preceptor competencies can inform preceptor preparation courses and identify needs for continuing education of preceptors. J Contin Educ Nurs. 2018;49(5):233-240.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…The qualitative synthesis showed that mentors are mainly assigned based on their specific characteristics, seniority and abilities. This is consistent with other studies (Geraci & Thigpen, ; L'Ecuyer, Hyde, & Shatto, ; Sambunjak, Straus, & Marusic, ). For example, most enrolled nurses (ENs) receive lower levels of education than advanced practice nurses (APNs) (Endacott et al, ; Harbman et al, ), but the work of ENs is increasingly complex when they provide direct care to residents and are involved in an educational role (Gibson & Heartfield, ).…”
Section: Discussionsupporting
confidence: 93%
“…The qualitative synthesis showed that mentors are mainly assigned based on their specific characteristics, seniority and abilities. This is consistent with other studies (Geraci & Thigpen, ; L'Ecuyer, Hyde, & Shatto, ; Sambunjak, Straus, & Marusic, ). For example, most enrolled nurses (ENs) receive lower levels of education than advanced practice nurses (APNs) (Endacott et al, ; Harbman et al, ), but the work of ENs is increasingly complex when they provide direct care to residents and are involved in an educational role (Gibson & Heartfield, ).…”
Section: Discussionsupporting
confidence: 93%
“…Of the 41 included articles, 26 were conducted in the United States (9, 10, 25, 26, 28-31, 33-36, 38-40, 44-48, 50-52, 56, 59) , three in Canada (8,11,54) , two in Taiwan (42,43) , two in Iran (27) , and one each in Thailand (57) , Ethiopia (53) ,Saudi (24) , Brazil (37) , Australia (49) , Sweden (58) , Belgium (55) and the United Kingdom (32) . Seventeen were based on preceptorship/education in medicine (10, 31, 32, 35, 44, 46, 50-52, 54-56, 58-60) , twelve in pharmacy (9, 11, 24-26, 30, 33, 34, 36, 38, 53, 57) , and eleven in nursing (8,27,28,37,(40)(41)(42)(43)(47)(48)(49) and one in dentistry (45) . There were twelve quantitative studies (25,26,30,33,35,39,46,47,49,53,57) , ten qualitative studies (29,34,37,41,42,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seventeen were based on preceptorship/education in medicine (10, 31, 32, 35, 44, 46, 50-52, 54-56, 58-60) , twelve in pharmacy (9, 11, 24-26, 30, 33, 34, 36, 38, 53, 57) , and eleven in nursing (8,27,28,37,(40)(41)(42)(43)(47)(48)(49) and one in dentistry (45) . There were twelve quantitative studies (25,26,30,33,35,39,46,47,49,53,57) , ten qualitative studies (29,34,37,41,42,44,45,48,58,59) , three mixed methods (43,50,51) , four descriptive papers that did not report results (36,38,40,56) , five papers concerned with validity testing (28,31,52,54,55) and seven papers describing consensus building, three with Delphi approaches (...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 41 included articles, 26 were conducted in the United States (6, 7, 22, 23, 25-28, 30-33, 35-37, 41-45, 7 47-49, 53, 56) , three in Canada (5,8,51) , two in Taiwan (39,40) , two in Iran (24) , and one each in Thailand (54) , Ethiopia (50) ,Saudi (21) , Brazil (34) , Australia (46) , Sweden (55) , Belgium (52) and the United Kingdom (29) . Seventeen were based on preceptorship/education in medicine (7, 28, 29, 32, 41, 43, 47-49, 51-53, 55-57) , twelve in pharmacy (6, 8, 21-23, 27, 30, 31, 33, 35, 50, 54) , and eleven in nursing (5,24,25,34,(37)(38)(39)(40)(44)(45)(46) and one in dentistry (42) . There were twelve quantitative studies (22,23,27,30,32,36,43,44,46,50,54) , ten qualitative studies (26,31,34,38,39,41,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seventeen were based on preceptorship/education in medicine (7, 28, 29, 32, 41, 43, 47-49, 51-53, 55-57) , twelve in pharmacy (6, 8, 21-23, 27, 30, 31, 33, 35, 50, 54) , and eleven in nursing (5,24,25,34,(37)(38)(39)(40)(44)(45)(46) and one in dentistry (42) . There were twelve quantitative studies (22,23,27,30,32,36,43,44,46,50,54) , ten qualitative studies (26,31,34,38,39,41,42,45,55,56) , three mixed methods (40,47,48) , four descriptive papers that did not report results (33,35,37,53) , five papers concerned with validity testing (25,28,49,51,52) and seven papers describing consensus building, three with Delphi approaches…”
Section: Study Characteristicsmentioning
confidence: 99%